Implementing the 5-Table Posyandu Model as an Intervention for Adolescent Anemia Prevention: An Experimental Study - Kaung Zaw; Putri Eka Sejati; Salsabilla Aprillita Riandi (Universitas STRADA Indonesia, 2026)
Methods: Using a quasi-experimental one-group pretest-posttest design, 30 adolescent girls (aged 12–18) in the Sebulu I Health Centre work area were selected using purposive sampling. Knowledge was measured using questionnaires before and after the 5-table intervention. Results: The mean knowledge score significantly increased from 5.63 (pretest) to 11.83 (posttest). Respondents in the